Complaint Speech Act Of Hotel And Restaurant Guests - Suryawan, I Nengah; Putra Yadnya, Ida Bagus; Puspani, Ida Ayu Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2016)
This paper is aimed at analyzing how complaint speech act of hotel and restaurant guests are performed and responded based on categories of speech acts and how they are performed considering the aspects of acts: locutionary, illocutionary, and perlocutionary. The method and technique of collecting data in this study is documentation method in which the data were collected using the technique of note taking and were qualitatively analyzed. The findings show that complaint of hotel and restaurant services stated by the guest was intended to have a good response of the server about the complaint conveyed. Based on the categories of speech, the guests used expressive and declarative speech acts to express complaints and the server used expressive and commissive speech acts to respond complaints. Complaints of hotel and restaurant guests involved three kinds of acts: locutionary, illocutionary, and perlocutionary. Locutionary act is the utterance conveyed by the guest to show sense that he or she was not happy with something. Illocutionary act shows that what the guest wanted the server to do concerning his complaints through speech. Perlocutionary act is a kind of action taken by the server to respond the complaint speech act stated by guests
Keywords: complaint speech act, hotel and restaurant guests, categories of speech acts, complaint, aspects of acts.